Evaluation of School Learning Continuity Plan (LCP) Utilizing Context, Input, Process, and Product (CIPP) Model - Yunzal Jr, Ananias; Hungo, Melbert; Casinillo, Leomarich F (Jurnal Pendidikan Indonesia, 2024)
The pandemic disrupted educational systems globally, prompting the need for alternative learning modalities like online, modular, and blended learning. The SLCP, particularly within the context of a school in Region 8, integrates these modalities to address essential learning competencies. This research paper aimed to evaluate the school Learning Continuity Plan (LCP) through its School Continuity Learning Plan Program using (CIPP) model of evaluation. Employing a qualitative design, data were gathered through purposive interviews with 1 non-teaching personnel, 1 department head, and 3 teachers and an analysis of the approved LCP road-map. Findings revealed comprehensive alignment with the evaluation model domains, though certain areas required revisiting for improvement. The study advocated for the administration's holistic consideration, especially recognizing teachers as front line contributors to the LCP. Their pivotal role in the design and planning phases was emphasized for the effective mechanization of the school LCP. Hence, it was concluded that educational administrators should prioritize collaboration with teachers and consider their perspectives to enhance the overall quality and functionality of the LCP. Moreover, the study recommended organizational consideration, valued teachers in school LCP, prioritized health, integrated modalities, and emphasized quality learning with metrics in LCP.